(untitled) (Journal of Atomic and Molecular Sciences, 2012)
The properties of strong-coupled magnetopolaron are studied by using the linear combination operator and unitary transformation methods in triangular quantum well (TQW). Considering the influence of the spin, the ground-state energy of polaron is obtained. The expressions for the ground-state energy as functions of the vibration frequency, the electron areal density and the magnetic field were derived. Numerical calculation on the TlBr TQW, as an example, is performed and the results show that the ground-state energy is composed of three parts. And the ground-state energy of magnetopolaron increase with enlarging the magnetic field and the electron areal density.